2021
DOI: 10.1088/1755-1315/936/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Constant 12 and reflexivity 472319 hahslm on the geography of the earth in the economic era of covid

Abstract: The purpose of this research is to analyze the geographical shape of the earth’s face with the 472319 Hahslm patterns in geomorphology. Earth undergoes the process of forming water and soil so that it becomes a continent and an archipelago. The composition of the sea and land is 7:3. The object of this study is the shape of the sea and land on earth and the Quran 13.31. This research was conducted by studying literature from books, journals, electronic media, and earth globes, and world atlases. The methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Bridge is the link between the carapace and the plastron. The bridge is composed of two layers, namely the outer layer which has a structure of large and hard scales, while the inner layer has a structure in the form of tightly packed plates (Mochamad, 2021). Based on the results of morphometric measurements of the sulcata tortoise group, it was shown that the C group had a larger morphometric size than the B and A turtles, this was due to age and growth factors.…”
Section: Jurnal Pembelajaran Dan Biologimentioning
confidence: 99%
“…Bridge is the link between the carapace and the plastron. The bridge is composed of two layers, namely the outer layer which has a structure of large and hard scales, while the inner layer has a structure in the form of tightly packed plates (Mochamad, 2021). Based on the results of morphometric measurements of the sulcata tortoise group, it was shown that the C group had a larger morphometric size than the B and A turtles, this was due to age and growth factors.…”
Section: Jurnal Pembelajaran Dan Biologimentioning
confidence: 99%